Myelin oligodendrocyte glycoprotein-associated disease is associated with BANK1, RNASET2 and TNIP1 polymorphisms - Shu, Yaqing; Ma, Xiaoyu; Chen, Chen; Wang, Yuge; Sun, Xiaobo; Zhang, Liang; Lu, Zhengqi; Petersen, Frank; Qiu, Wei; Yu, Xinhua (Journal of neuroimmunology, 2022)
Here we aimed to compare association of common immune-related genetic variants with three autoimmune central nervous system (CNS) demyelinating diseases, namely myelin oligodendrocyte glycoprotein-associated disease (MOGAD), multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). In this retrospective cross-sectional study, 26 common immune-related single nucleotide polymorphisms were genotyped in 102 patients with MOGAD, 100 patients with MS, 198 patients with NMOSD and 541 healthy control subjects recruited from Guangzhou, China. Among all tested genetic variations, one polymorphism, B cell scaffold protein with ankyrin repeats 1 (BANK1) rs4522865 was associated with multiple disorders, namely MOGAD (OR = 1.94, 95% CI:1.19–3.17, P = 0.0059) and NMOSD (OR = 1.69, 95% CI:1.17–2.45). Besides BANK1 rs4522865, two other non-HLA loci, ribonuclease T2 (RNASET2) rs9355610 (OR = 0.47, 95% CI: 0.26–0.85) and TNFAIP3 interacting protein 1 (TNIP1) rs10036748 (OR = 1.76, 95% CI: 1.16–2.71), were associated with MOGAD. In addition, NMOSD was associated with signal transducer and activator of transcription 4 (STAT4) rs7574865 (OR = 1.58, 95% CI: 1.12–2.24) and general transcription factor Iii (GTF2I) rs73366469 (OR = 1.60, 95% CI:1.12–2.29), while MS was associated with a killer cell lectin like receptor G1 (KLRG1) rs1805673 (OR = 0.61, 95% CI: 0.40–0.94) and T-box transcription factor 21 (TBX21) rs17244587 (OR = 2.25, 95% CI: 1.25–4.06). The current study suggests for the first time three non-HLA susceptibility loci for MOGAD. In addition, comparison of association of 26 immune-related polymorphisms with three autoimmune CNS demyelinating diseases demonstrates substantial difference in genetic basis of those disorders. •Myelin oligodendrocyte glycoprotein-associated disorders is associated with BANK1, RNASET2 and TNIP1.•Neuromyelitis optica spectrum disorder is associated with BANK1, STAT4 and GTF2I.•There are substantial difference in genetic basis between autoimmune CNS demyelinating disorders.